Znaczenie kulturowego modelu niepełnosprawności dla współczesnej pedagogiki specjalnej - Twardowski, Andrzej (Kultura-Społeczeństwo-Edukacja, 2024)
The aim of this study is to present the cultural model of disability and its consequences for contemporary special education. It began by presenting three models of disability – medical, social and cultural. Next, the four main assumptions constituting the theoretical framework of the cultural model of disability were characterized: (1) cultures differ in their views on the human body; (2) people perceive reality through the prism of their culture and experiences acquired in it; (3) disability may have different meanings depending on what kind of discourse onstitutes its meaning; (4) the current epistemological perspective in the approach to the problem of disability should be reversed. The second part of the paper discusses the most important implications of the cultural model of disability for the theory and practice of special education.